PENERAPAN MODEL PEMBELAJARAN TALKING STICK BERBANTUAN FLASH CARD UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATERI KAWAN SEIRING MATA PELAJARAN BAHASA INDONESIA - Lukmanto Adoe; Lamsike Pateda; Sitti Rahmawati Talango (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine whether the Talking Stick Model assisted by Flash Cards can improve the Learning Activity of Grade III Students at SDN 2 Linawan. This type of research is classroom action research. The subjects of this study were 24 grade III students at SDN 2 Linawan. The data analysis techniques used in this study were analysis of test results and analysis of observation results. Based on the results of the study, it can be concluded that learning Indonesian using the Talking Stick learning model assisted by Flash Cards can improve the Learning Activity of Grade III Students at SDN 2 Linawan. This is indicated by the improvement in student learning outcomes in cycles I and II. In cycle I, 11 students were categorized as having achieved the Minimum Competency (KKM) with a percentage of 45.8% and in cycle II, 22 students were categorized as having achieved the Minimum Competency (KKM) with a percentage of 91%. This is because in cycle II, students have begun to improve in the learning process, most of the students have maximized their reading comprehension. So, student learning in cycle II has reached the Minimum Competency (KKM) value or the specified performance indicators. Thus, the hypothesis in this study is that using the Talking Stick learning model assisted by Flash Cards can increase the learning activity of grade III students at SDN 2 Linawan.